Formorsaneleotris hualienensis, a new genus and species of inland water sleeper (Teleostei: Eleotridae) from eastern Taiwan - Chen, I-Shiung (Zootaxa, 2024)
A very unusual sleeper gobioid fish was obtained from netting in the inland waters of the Hualien River basin in eastern Taiwan. This new genus and species of sleeper has only been collected from Taiwan. Formosaneleotris hualianensis n. gen. & n. sp. can be well distinguished from other sleepers by a unique combination of the following characters: (1) fins: no first dorsal fin; second dorsal fin I/8; anal fin I/8; pectoral fin 13–14; (2) squamation: entirely body naked; (3) vertebral count: 10 + 14 = 24; (4) branchiostegal rays 6; (5) head lacking any canal and pore with longitudinal-like infraorbital sensory papillae; and (6) specific coloration: body and head bloody red entirely; one thin deep red infraorbital stripe to upper lip.